Amorphous silica-alumina containing medium-strong Bronsted acid as well as preparation method and application of amorphous silica-alumina
By regulating the preparation process of amorphous silicon-aluminum, it improves its acidic characteristics, forms a carrier rich in medium-strong B acid, and loads metals, solving the problem of weak acidity, significantly improving the activity of FTS wax hydrocracking reaction and diesel recovery Rate.
Patent Information
- Application Number
- CN202410952221.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2024-12-27
AI Technical Summary
The existing amorphous silicon-aluminum support has weak acidity, which affects its catalyst performance, especially in the FTS wax hydrocracking reaction, which is difficult to achieve efficient conversion.
By adjusting and controlling the crystallization treatment time, temperature and aluminum source during the preparation process, an amorphous silicon-aluminum carrier rich in medium-strong B acid is prepared, and the acidic characteristics are improved through ammonia exchange treatment to form a four-membered ring, five-membered ring or ZSM. -5 nano-scale crystal nuclei of the molecular sieve, supported by Ru, Pt or Pd metals, to make a hydrocracking catalyst.
It significantly improves the reactivity and diesel yield of the catalyst, simplifies the preparation process, and effectively regulates the texture properties and acidic characteristics of the carrier.
Smart Images

Figure CN119186544A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst carrier material synthesis, and specifically relates to a catalyst carrier material containing a medium-strength Amorphous silicon-alumina containing acid and its preparation method and application. Background Art
[0002] FTS wax is one of the main products of the Fischer-Tropsch Synthesis (FTS) process, and its content accounts for more than 60% of the total product. FTS wax has a simple structure, mainly composed of paraffins and a small amount of isomeric hydrocarbons, and basically does not contain cycloalkanes and aromatics. It has the advantages of being sulfur-free and nitrogen-free, and is a high-quality raw material for producing high cetane number and ultra-clean middle distillates (diesel). However, the terminal distillation point of FTS wax reaches 800°C. The structural characteristics of paraffins determine that it is relatively easier to crack during the hydrocracking reaction, and it must undergo secondary cracking to generate middle distillate oil with a distillation range of 150 to 370°C; the traditional hydrocracking catalyst based on petroleum-based heavy distillate oil (rich in cycloalkanes and aromatics) is not suitable for FTS wax from the design principle. Therefore, it is of great practical significance to design a hydrocracking catalyst for FTS wax as a raw material to achieve efficient conversion to middle distillate oil.
[0003] Hydrocracking catalysts are typical metal-acid bifunctional catalysts that follow the classic bifunctional catalytic mechanism. The metal components are generally VIII and VIB elements. The research is becoming more mature at this stage, and the carrier material has always been the focus of researchers due to its variable structure and properties. Amorphous silica-alumina (ASA) with an open structure has been widely used in macromolecular catalysis fields such as petrochemicals, fine chemicals and biorefining due to its high specific surface area, large pore volume and mesoporous structure. Studies have shown that Bronsted acid ( B) is the main active center of the hydrocracking reaction. However, the weak acidity and low acid content caused by the amorphous structure of ASA have become the core factors affecting its catalyst performance. Therefore, effective regulation of the B acid properties of ASA is a key issue that needs to be solved urgently.
[0004] The acidic properties of ASA, especially the properties of B acid, are closely related to its preparation method. The patent with application number CN116328851A discloses a B acid-containing hydroconversion catalyst carrier and its preparation and application. First, the pseudo-boehmite is dissolved with an acid solution to prepare a homogeneous aluminum sol. Then, a certain concentration of NH4BF4 solution is added dropwise under stirring conditions to form a gel. Subsequently, the gel is vacuum dried, calcined, and the like to obtain an alumina material rich in weak and medium strength B acid. The carrier is loaded with Ni-W metal to prepare a hydroconversion catalyst, and applied to the modeling reaction of hydrodesulfurization of n-decane solution of 4,6-dibenzothiophene (DBT) and quinoline (Q) to evaluate the catalytic performance. The results show that the catalyst activity is significantly improved, however, the liquid yield does not change significantly. At the same time, the above preparation method is relatively cumbersome, and it mainly regulates weak and medium strength B acid. Summary of the invention
[0005] The object of the present invention is to provide a medium-strength Amorphous silica-alumina of acid, its preparation method and application, by regulating the crystallization treatment time, crystallization temperature and aluminum source in the preparation process, the acid characteristics of ASA (especially the medium-strong B acid properties) are effectively adjusted; the hydrocracking catalyst prepared from the ASA carrier shows good reaction activity and diesel yield in the FTS wax hydrocracking reaction.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In the first aspect, the present invention provides a medium-strength The method for preparing acidic amorphous silicon-aluminum comprises the following steps:
[0008] Step 1: mixing an aluminum source, a silicon source, an inorganic base, a template and water in a certain molar ratio to obtain a precursor solution;
[0009] Step 2: subjecting the precursor solution to aging, crystallization, solid-liquid separation, drying, and calcination treatments in sequence to obtain a sodium-type ASA sample;
[0010] Step 3: subjecting the sodium-type ASA sample to an ammonia exchange treatment, and then to separation, drying and calcination treatment to obtain an ASA carrier containing a medium-strong B acid;
[0011] Wherein, in step 2, the crystallization temperature is 100-130° C., and the crystallization time is 10-60 h.
[0012] In some embodiments, in step 1, the molar ratio of the aluminum source, silicon source, inorganic base, template and water is 1: (20-30): (4-6): (10-12): (1500-2500); preferably, the molar ratio of the aluminum source, silicon source, inorganic base, template and water is 1: 25: 5.1: 10.7: 2000;
[0013] Or, the aluminum source is selected from one or more of aluminum isopropoxide, pseudo-boehmite, aluminum nitrate, sodium aluminate, hydrated aluminum oxide, aluminum acetylacetonate, or aluminum hydroxide;
[0014] Or, the silicon source is selected from one or more of tetraethyl orthosilicate, silica sol, water glass or white carbon black; preferably, the silicon source is silica sol;
[0015] Or, the inorganic base is selected from one or more of potassium hydroxide or sodium hydroxide;
[0016] Alternatively, the template agent is selected from one or both of tetrapropylammonium hydroxide and tetraethylammonium hydroxide.
[0017] In some embodiments, in step 1, the mass percentage of SiO2 in the silica sol is 10% to 50%; preferably, the mass percentage of SiO2 is 30%;
[0018] Alternatively, the mass percentage of the tetrapropylammonium hydroxide or tetraethylammonium hydroxide is 20% to 40%; preferably, the mass percentage of the tetrapropylammonium hydroxide or tetraethylammonium hydroxide is 25%.
[0019] In some embodiments, in step 1, the mixing process of the aluminum source, silicon source, inorganic base, template and water is:
[0020] (1) mixing an inorganic base with water to obtain an inorganic base solution, adding an aluminum source to the inorganic base solution, and stirring and mixing to obtain a solution A;
[0021] (2) adding a template to solution a, stirring and mixing to obtain solution b;
[0022] (3) Add the silicon source dropwise to solution b, and after stirring and mixing thoroughly, obtain a precursor solution.
[0023] In some embodiments, in step 2, the aging temperature is 10 to 60° C., and the aging time is 5 to 24 hours;
[0024] Or, the drying temperature is 100-130°C and the drying time is 3-10 hours;
[0025] Alternatively, the calcination temperature is 480-650° C., and the calcination time is 3-5 hours.
[0026] In some embodiments, in step 3, during the ammonia exchange treatment, the mixed solid-liquid ratio is 1:10 to 1:20;
[0027] Or, the concentration of NH4Cl solution is 0.5~1.0M;
[0028] Or, the temperature of the ammonia exchange treatment is 30 to 90°C, the time is 1 to 5 hours, and the number of times is 1 to 3 times;
[0029] Or, the drying temperature is 100-130°C and the drying time is 3-10 hours;
[0030] Alternatively, the calcination temperature is 480-550° C., and the calcination time is 3-5 hours.
[0031] In a second aspect, the present invention provides a medium-strength Amorphous silicon-alumina containing acid is prepared by the preparation method of the first aspect, wherein the medium-strong The amorphous silicon-aluminum containing acid is formed by stacking secondary structural units of molecular sieves, and the secondary structural units containing molecular sieves are four-membered rings, five-membered rings, six-membered rings or nano-scale crystal nuclei of ZSM-5 molecular sieves formed by the interaction of Al and Si.
[0032] In some embodiments, the medium-strength The acid-containing amorphous silica-alumina has a 200°C infrared B acid amount of 40-55% of the infrared acid amount, a 200°C infrared outer surface B acid amount of 10-45% of the infrared acid amount, a 200°C infrared micropore B acid amount of 1-40% of the infrared acid amount; a 350°C infrared B acid amount of 3-20% of the infrared acid amount; preferably, a 200°C infrared B acid amount of 45-50% of the infrared acid amount; a 200°C infrared outer surface B acid amount of 35-45% of the infrared acid amount; a 200°C infrared micropore B acid amount of 1-6% of the infrared acid amount.
[0033] In a third aspect, the present invention provides a hydrocracking catalyst, comprising a metal and the medium-strength Amorphous silica-alumina with acid, the metal is one or more of Ru, Pt or Pd; the loading amount of the metal is 0.2-2.0wt%.
[0034] In a fourth aspect, the present invention provides an application of a hydrocracking catalyst in a FTS wax hydrocracking reaction.
[0035] The beneficial effects of the above embodiments of the present invention are as follows:
[0036] (1) The ASA carrier prepared by the present invention has a mesoporous structure and is rich in medium-strong B acid, and has high catalytic reaction activity.
[0037] (2) The preparation method of the ASA carrier of the present invention is simple and controllable, and can effectively regulate its textural properties and acidic characteristics (especially B acid properties).
[0038] (3) The ASA carrier-loaded metal-type hydrocracking catalyst prepared by the present invention can significantly improve the reaction activity and diesel yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0040] Figure 1 is the XRD spectrum of ASA prepared in Examples 1 to 7 of the present invention;
[0041] Figure 2 is the Raman spectra of ASA prepared in Examples 1, 4 to 7 of the present invention;
[0042] Figure 3 are SEM and TEM images of ASA prepared in Examples 1, 2, 4, 5, and 7 of the present invention, wherein (a-1) to (a-5) are Example 4, (b) Example 2, (c) Example 1, (d) Example 5, and (e) Example 7;
[0043] Figure 4 This is the N2 physical adsorption-desorption characterization spectrum of ASA prepared in Example 7 of the present invention;
[0044] Figure 5 is the Py-FTIR spectrum of ASA prepared in Examples 1, 4 to 7 of the present invention tested after desorption at 200°C;
[0045] The diagrams are for illustrative purposes only. DETAILED DESCRIPTION
[0046] As mentioned in the background, the preparation method of the ASA carrier directly affects the physical and chemical properties of ASA, especially the Br acid properties. In the process of FTS wax hydrocracking to produce diesel, the activity of the catalyst is mainly related to the Br acid properties of the outer surface of the ASA carrier: the higher the content of strong Br acid in the outer surface, the higher the activity of the catalyst. At the same time, the presence of the microporous structure of the ASA carrier is not conducive to the improvement of diesel selectivity. The lower the content of Br acid sites in the micropores, the higher the selectivity and yield of diesel.
[0047] According to the applicant's previous research work (the effect of the acidity of amorphous silica-alumina carrier on diesel selectivity in Fischer-Tropsch wax hydrocracking reaction), the method of washing away Na ions to release acid sites by gradient ammonia exchange was used to achieve the regulation of B acid sites in Pt / ASA catalysts and the improvement of catalyst activity and selectivity. However, the ASA carrier prepared by this method cannot avoid the presence of sodium ions, which affects the reaction process and has a greater corrosive effect on the reaction equipment.
[0048] 1. Preparation of ASA vector
[0049] Example 1
[0050] (1) Weigh 7.7 g of NaOH and add it to a 2 L beaker filled with 810 g of deionized water. Place it in a 30°C water bath and stir it thoroughly until it is completely dissolved. Then add 5.9 g of NaAlO2 solid powder and continue stirring until the solution is clear to obtain solution a.
[0051] (2) Add 313.4 g of TPAOH solution (mass fraction: 25%) to solution a and mix well to obtain solution b;
[0052] (3) Add 360 g of alkaline silica sol (SiO2 mass fraction: 30%) dropwise to solution b, and after vigorous stirring and thorough mixing, obtain an initial milky white sol;
[0053] (4) The milky white sol was aged in a water bath at 30°C for 12 h, then transferred to a static reactor with a capacity of 800 ml and crystallized at 115°C for 55 h;
[0054] (5) The crystallized sample was taken out from the static reactor, filtered, and washed with deionized water until the filtrate was neutral. The sample was then placed in an oven at 120°C to be fully dried, and then moved to a muffle furnace at 550°C for calcination for 4 h to remove the template, and finally a sodium-type ASA carrier was obtained;
[0055] (6) Ammonia exchange treatment was performed at a solid-liquid ratio of 1:20. After mixing sodium ASA with 0.5 M NH4Cl solution, the mixture was exchanged in a water bath at 80°C for 2 h. The ammonia exchange treatment was repeated twice to obtain an ASA sample containing medium-strong B acid.
[0056] Example 2
[0057] The difference from Example 1 is that in step (4), the crystallization treatment time is 47 hours. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0058] Example 3
[0059] The difference from Example 1 is that in step (4), the crystallization treatment time is 40 hours. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0060] Example 4
[0061] The difference from Example 1 is that in step (4), the crystallization treatment time is 20 hours. The other preparation steps are the same as those in Example 1 and will not be repeated here.
[0062] Example 5
[0063] The difference from Example 4 is that in step (1), 17.0 g of aluminum isopropoxide solid powder is added to replace 5.9 g of NaAlO2 solid powder. The other preparation steps are the same as those in Example 4 and will not be repeated here.
[0064] Example 6
[0065] The difference from Example 4 is that in step (1), 23.3 g of aluminum acetylacetonate solid powder is added to replace 5.9 g of NaAlO2 solid powder. The other preparation steps are the same as those in Example 4 and will not be repeated here.
[0066] Example 7
[0067] The difference from Example 6 is that in step (4), the crystallization treatment temperature is 125° C. and the crystallization treatment time is 10 h. The other preparation steps are the same as those in Example 6 and will not be repeated here.
[0068] The XRD spectra of the samples prepared in Examples 1 to 7 of the present invention are as follows: Figure 1 As shown, the samples prepared in Examples 1 to 7 all have an amorphous broad peak in the range of 15 to 30°, and no characteristic diffraction peaks of SiO2 or Al2O3 appear, indicating that the samples prepared in Examples 1 to 7 are all amorphous ASA. The adjustment of the crystallization treatment time (20h, 40h, 47h and 55h), aluminum source (sodium metaaluminate, aluminum isopropoxide and aluminum acetylacetonate) and crystallization treatment temperature (115°C, 125°C) did not affect the amorphous structure of ASA.
[0069] The SEM and TEM images of ASA prepared in Examples 1, 2, 4, 5 and 7 of the present invention are as follows: Figure 3 As shown, Figure 3The SEM spectrum of (a)-1 shows that the sample prepared in Example 4 is a solid particle with irregular shape. The distribution of Si and Al in Example 4 was tested by TEM's X-ray photoelectron spectroscopy, and it was found that Si and Al were uniformly mixed at the nanoscale. The samples prepared in Examples 1, 2, 4, 5 and 7 were characterized by TEM electron diffraction. It can be seen that although no visible lattice appeared in the samples of Examples 1, 2, 4 and 5, different plane distances were observed, indicating that the molecular sieve secondary structural units in the samples were gradually ordered. In Example 7, an organic aluminum source was used, and electron diffraction spots appeared in the sample crystallized at 125°C, indicating the formation of an ordered structure. Combined with the characterization analysis of XRD and Raman, it was found that with the extension of the crystallization time, the molecular sieve secondary structural units in the ASA sample assembled to form a nano-sized ZSM-5 molecular sieve below the XRD detection limit.
[0070] The N2 physical adsorption-desorption characterization spectrum of ASA prepared in Example 7 of the present invention is as follows Figure 4 In the precursor system shown in FIG. 1 , under the action of the organic template, Al in the solution interacts with Si to form molecular sieve secondary structural units such as 4R, 5R, and 6R, and even nano-scale crystal nuclei of ZSM-5 molecular sieves. The Raman spectra of ASA prepared in Examples 1, 4 to 7 of the present invention are shown in FIG. Figure 2 As shown in the figure, with the extension of crystallization treatment time, ordered secondary structural units gradually appeared in the ASA sample. It can be seen that under the condition of little structural change, increasing the crystallization treatment temperature and using an organic aluminum source are conducive to promoting the appearance of molecular sieve secondary structural units. This shows that the ASA sample has abundant mesopores and a mesopore pore size distribution of 10 to 15 nm.
[0071] Based on the above analysis, it can be seen that by adjusting the crystallization treatment time, crystallization treatment temperature and aluminum source, the molecular sieve secondary structural units such as 4R, 5R, and 6R in the ASA sample can be regulated, thereby affecting the content of molecular sieve secondary structural units containing bridged hydroxyl groups in ASA, and further affecting the B acid content in ASA.
[0072] The Py-FTIR spectra of the ASA samples prepared in Examples 1 to 7 of the present invention after desorption at 200°C are as follows: Figure 5 The acid type, acid content and B acid characteristics at different positions in the ASA sample are listed in Table 1. Among them, the acid measured after desorption at 200℃ is medium-strong acid, and the acid measured after desorption at 350℃ is strong acid.
[0073] Table 1 Acid site contents of different types and positions on ASA (μmol Py / g)
[0074]
[0075] The study found that with the extension of crystallization time, the overall content (200℃) of Br and Lewis acid (L) gradually increased; the use of organic aluminum as an aluminum source and the appropriate increase in the crystallization temperature are conducive to the increase of Br content. The samples were characterized by conventional Py-FTIR, and after desorption treatment at 200℃ and 350℃, the measured Py adsorption amount was defined as the overall medium-strong Br (200℃) and strong Br (350℃) content, respectively.
[0076] The location of the B acid in the ASA sample is crucial for the acid-catalyzed reaction of macromolecules (such as FTS wax). In order to distinguish and quantify the B acid sites inside and outside the micropores of the sample, a dual probe molecule test FTIR characterization method (DMPy-Py-IR) was used to detect the in situ adsorption equilibrium of 2,6-dimethylpyridine (DMPy) and then adsorption of Py. Due to the shape selectivity of the micropore channel, DMPy with a larger kinetic size (0.67nm) is difficult to enter the micropore channel of ASA. Therefore, after the in situ adsorption equilibrium of the ASA sample in the DMPy atmosphere, the probe molecule DMPy occupies all the B acid sites on its outer surface; in the subsequent Py-FTIR test, the Py adsorption amount is defined as the B acid content in the micropores. After desorption treatment at 200℃ and 350℃, the measured Py adsorption amounts were defined as the medium-strong B acid (200℃) and strong B acid (350℃) contents in the micropores, respectively. Since the above-mentioned Py-FTIR and DMPy-Py-IR characterization test procedures are basically the same, and the quantitative unit is μmol Py / g, the acid B content on the outer surface of the sample can be obtained by simple subtraction calculation. It can be seen that the content of medium-strong B acid (200°C) in the micropores changes in Example 2≈Example 1>Example 3>Example 5>Example 6>Example 4>Example 7. The order of change of the content of medium-strong B acid (200°C) on the outer surface of the sample is Example 7>Example 6>Example 5>Example 1≈Example 4>Example 3>Example 2.
[0077] 2. Preparation and application of hydrocracking catalyst
[0078] Preparation of hydrocracking catalyst: The metal is loaded onto the ASA carrier prepared by the present invention and the commercially available ASA carrier (Siral40) by an equal volume impregnation method, left to stand at room temperature for 12 hours, dried at 120°C, and then placed in a muffle furnace for calcination at 420°C for 4 hours to obtain a hydrocracking catalyst. The metal is one or more of Ru, Pt or Pd, preferably Pt; the loading amount of the metal is 0.2-2.0wt%, preferably 0.5wt%.
[0079] The present invention adopts the above preparation method to load Pt onto the ASA carrier prepared by the present invention and the commercially available Siral40 carrier (comparative example), and the loading mass is 0.5wt%.
[0080] Hydrocracking performance of the catalyst: Using FTS wax as the raw material, 2.8 g of the catalyst was loaded into a continuous flow fixed bed reactor, and the catalyst was reduced with pure H2 at 380°C and atmospheric pressure for 6 hours, and then cooled to 300°C to evaluate the hydrocracking performance of the catalyst. Among them, FTS wax is a mixture with a carbon number ranging from 20 to 120.
[0081] The hydrocracking reaction conditions are: the mass space velocity of FTS wax is 0.5~3h -1 ; The molar ratio of H2 to FTS wax is 0.2-6.0:1; the reaction pressure is 1-7 MPa, preferably 4 MPa; the reaction temperature is 300-500°C.
[0082] The results of the evaluation of the above catalysts for FTS wax hydrocracking are shown in Table 2, with emphasis placed on the catalytic performance of the catalysts when the conversion rate was about 50%.
[0083] Table 2 Catalytic performance evaluation results of catalysts
[0084]
[0085] #imgpt11#
[0086] It can be seen that when the conversion rate of FTS wax is 50%, the reaction temperature required for each catalyst decreases in the order of Comparative Example 1> Example 2> Example 3> Example 1≈ Example 4> Example 5> Example 6> Example 7, which is consistent with the variation law of the strong B acid content on the outer surface of the carrier in Table 1, that is, the higher the strong B acid content on the outer surface of the carrier, the lower the reaction temperature required to achieve a similar conversion rate, and the higher the catalyst activity. The B acid in the ASA carrier prepared by the present invention is derived from the skeleton Al, and the B acid exists both on the outer surface of the ASA carrier and in the micropores. Although FTS wax can enter the interior of the micropores, it needs to overcome a large diffusion energy barrier before it can enter the interior of the micropores to react. Therefore, FTS wax is more inclined to react at the B acid site on the outer surface of the catalyst, that is, the higher the content of medium-strong B acid on the outer surface, the faster the protonation rate of the olefin intermediate, and the higher the activity of the catalyst.
[0087] The presence of Br acid sites in the micropores of ASA is not conducive to the improvement of diesel selectivity. The higher the content of medium-strong Br acid in the micropores, the lower the diesel selectivity, and more light components such as LPG and naphtha are produced. It is not difficult to see that most of the Br acid active sites in Example 7 of the present invention are located on the outer surface, and have a relatively minimum Br acid content in the micropores, as well as a uniform mesopore size distribution, so the diesel selectivity is the highest.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A medium-strength A method for preparing acid-free amorphous silicon-aluminum, characterized in that: The following steps are involved: Step 1: mixing an aluminum source, a silicon source, an inorganic base, a template and water in a certain molar ratio to obtain a precursor solution; Step 2: subjecting the precursor solution to aging, crystallization, solid-liquid separation, drying, and calcination treatments in sequence to obtain a sodium-type ASA sample; Step 3: subjecting the sodium-type ASA sample to an ammonia exchange treatment, and then to separation, drying and calcination treatment to obtain an ASA carrier containing a medium-strong B acid; Wherein, in step 2, the crystallization temperature is 100-130° C., and the crystallization time is 10-60 h.
2. The preparation method according to claim 1, characterized in that In step 1, the molar ratio of the aluminum source, silicon source, inorganic base, template and water is 1: (20-30): (4-6): (10-12): (1500-2500); preferably, the molar ratio of the aluminum source, silicon source, inorganic base, template and water is 1: 25: 5.1: 10.7: 2000; Or, the aluminum source is selected from one or more of aluminum isopropoxide, pseudo-boehmite, aluminum nitrate, sodium aluminate, hydrated aluminum oxide, aluminum acetylacetonate, or aluminum hydroxide; Or, the silicon source is selected from one or more of tetraethyl orthosilicate, silica sol, water glass or white carbon black; preferably, the silicon source is silica sol; Or, the inorganic base is selected from one or more of potassium hydroxide or sodium hydroxide; Alternatively, the template agent is selected from one or both of tetrapropylammonium hydroxide and tetraethylammonium hydroxide.
3. The preparation method according to claim 2, characterized in that: In step 1, the mass percentage of SiO2 in the silica sol is 10% to 50%; preferably, the mass percentage of SiO2 is 30%; Alternatively, the mass percentage of the tetrapropylammonium hydroxide or tetraethylammonium hydroxide is 20% to 40%; preferably, the mass percentage of the tetrapropylammonium hydroxide or tetraethylammonium hydroxide is 25%.
4. The preparation method according to claim 1, characterized in that: In step 1, the mixing process of the aluminum source, silicon source, inorganic base, template and water is: (1) mixing an inorganic base with water to obtain an inorganic base solution, adding an aluminum source to the inorganic base solution, and stirring and mixing to obtain a solution A; (2) adding a template to solution a, stirring and mixing to obtain solution b; (3) Add the silicon source dropwise to solution b, stir and mix thoroughly to obtain a precursor solution.
5. The preparation method according to claim 1, characterized in that: In step 2, the aging temperature is 10 to 60° C., and the aging time is 5 to 24 hours; Or, the drying temperature is 100-130°C and the drying time is 3-10 hours; Alternatively, the calcination temperature is 480-650° C., and the calcination time is 3-5 hours.
6. The preparation method according to claim 1, characterized in that: In step 3, during the ammonia exchange treatment, the mixed solid-liquid ratio is 1:10 to 1:20; Or, the concentration of NH4Cl solution is 0.5~1.0M; Or, the temperature of the ammonia exchange treatment is 30 to 90°C, the time is 1 to 5 hours, and the number of times is 1 to 3 times; Or, the drying temperature is 100-130°C and the drying time is 3-10 hours; Alternatively, the calcination temperature is 480-550° C., and the calcination time is 3-5 hours.
7. A medium-strength Amorphous silica-alumina of acid, characterized in that The medium-strength The amorphous silicon-aluminum containing acid is formed by stacking secondary structural units of molecular sieves, and the secondary structural units containing molecular sieves are four-membered rings, five-membered rings, six-membered rings or nano-scale crystal nuclei of ZSM-5 molecular sieves formed by the interaction of Al and Si.
8. The medium-strength Amorphous silica-alumina of acid, characterized in that The medium-strength The acid-containing amorphous silica-alumina has an infrared Br acid amount of 40-55% of the infrared acid amount at 200°C, an infrared outer surface Br acid amount of 10-45% of the infrared acid amount at 200°C, and an infrared micropore Br acid amount of 1-40% of the infrared acid amount at 200°C; an infrared Br acid amount of 350°C accounts for 3-20% of the infrared acid amount; preferably, the infrared Br acid amount at 200°C accounts for 45-50% of the infrared acid amount; the infrared outer surface Br acid amount at 200°C accounts for 35-45% of the infrared acid amount; and the Br acid amount in the infrared micropore Br acid accounts for 1-6% of the infrared acid amount.
9. A hydrocracking catalyst, characterized in that The hydrocracking catalyst comprises a metal and the medium-strength Amorphous silica-alumina with acid, the metal is one or more of Ru, Pt or Pd; the loading amount of the metal is 0.2-2.0wt%.
10. Use of the hydrocracking catalyst according to claim 9 in the hydrocracking reaction of FTS wax.
Citation Information
Cited By
A platinum-based Al2O3 / prototype and amorphous silica-alumina catalyst with tunable Brønsted acid, its preparation method and application
CN122937845A
